"Phytochemical and antimicrobial investigation of methanolic extract/fraction of Ocimum basilicum L.". (January 2021) - Rubab, Saima; Bahadur, Saraj; Hanif, Uzma; Durrani, Arjumand Iqbal; Sadiqa, Ayesha; Shafique, Sana; Zafar, Urooj; Shuaib, Muhammad; Urooj, Zara; Nizamani, Mir Muhammad; Iqbal, Shazia
Abstract: The crude solvent extracts of medicinal plants may be exploited as medicines for the betterment of human health. The isolation, purification and characterization of active phytochemical components and their mechanism of action is of predominant grandness. Keeping in view the importance of Ocimum basilicum, the present study was designed to document the phytochemical and antimicrobial activity of methanolic extract of O. basilicum stem. For this purpose dried powdered stem was extracted by successive solvent extraction using petroleum ether (for non-polar Fractions), chloroform (for constituents of intermediate polarities) and methanol (for polar constituents). Six major fractions Ob-1 to Ob-6 were separated from the methanolic extract of O. basilicum stem by column chromatography and purified by thin layer chromatography. All biological active and purified fractions were analyzed by Ultra Violet (UV) and Fourier Transform Infrared (FTIR) spectroscopy. These extracts were initially subjected to screening of antimicrobial activities. The results of the initial screening indicated that methanolic extract was more active than other solvent extracts. Antimicrobial potential of six major fractions Ob-1 to Ob-6 was determined against three species of gram-positive ( Clostridium defficile, Bacillus subtilis and Staphylococcus aureus ) bacteria, three species of gram-negative ( Escherichia coli, Salmonella typhi and Klebsiella pneumoniae ) bacteria and three species of fungi ( Aspergillus flavus, Aspergillus niger and Candida albicans ). All the six isolated fractions displayed well-marked antimicrobial potential against nine microbes. Ob-4, Ob-5 and Ob-6 appeared to be most potent than other fractions, but lesser than the standard antibiotics.